Adaptive reuse of colonial houses into cafés in Banda Aceh / Nurul Qaumarin, Cut Dewi and Izziah - Qaumarin, Nurul; Dewi, Cut; Izziah, Izziah (Universiti Teknologi MARA, Perak, 2025)
Aceh was one of the areas that experienced Dutch colonisation between 1873 and 1942. This period of Dutch rule was a significant one for the people of Aceh. The Dutch colonial period in Aceh is evidenced by the surviving relics of government bureaucratic buildings and colonial-style residences that were successfully established. The Dutch architectural heritage has been designated a cultural heritage in Banda Aceh. However, in accordance with the progression of time and the growing necessity for additional space, a considerable number of colonial-era residential structures have been dismantled. Presently, the only remaining vestiges of colonial-era residences are government-owned buildings. One method of preserving a building is through adaptive conservation, which involves reusing the building while making interior and exterior changes and maintaining the original shape and structure. Two cafés in Banda Aceh City have been created through the adaptive reuse of colonial residential houses. Two coffee houses, Café T36 Coffee and SOBA Café, are situated in the vicinity of Taman Sari. The objectives of this research are to identify and examine the implementation of the concept of adaptive reuse in colonial residential buildings that have been converted into cafés. The study was conducted using a descriptive qualitative method based on the philosophy of postpositivism, with data source triangulation techniques (on-site observation and in-depth structure interview) and theories that aim to analyse various perspectives. The findings demonstrate that the primary structural components, such as the frame and exterior facade, are preserved, while the interior and installation have been modified to align with the new functional requirements. The incorporation of historical elements, such as those reflective of the colonial architectural style, within the interior design can effectively convey the past. This can be achieved through the use of furniture styles, materials, floor patterns, wall ornaments, and ceiling designs that evoke the colonial era. In terms of spatial configuration, one of the most significant alterations is the creation of a more expansive public area to accommodate commercial activities.